SOME METHODS OF CATCHING THE VESPIDAE FAMILY AND SETTING TRAPS FOR THEM (Scientific journal of the Fergana State University, 2024)
This article is devoted to the methodology of catching and setting traps for representatives of the family of real wasps (Vespidae). This article describes in detail the methods of catching and protecting against wasps of the Vespidae family. The choice of trapping method depends on factors such as the species of Vespidae and the location of nests. It is important to consider safety precautions and local regulations when working with Vespidae species, as they can become aggressive when threatened.